Efektivitas Pembelajaran Berbasis Proyek dalam Meningkatkan Kreativitas Siswa di MIS MIMA 02 Darul Ulum Gumelar Balung Jember - Hidayah , Nurul; Rohmania , Nuzila; Aini , Nurul (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
Project-based learning is a method that emphasises students' active involvement in completing tasks that are relevant to the real world. This method aims to improve students' creativity, critical thinking skills, and collaboration. MIS MIMA 02 Darul Ulum Gumelar Balung Jember faces challenges in improving the creativity of students who still tend to be passive in learning. Therefore, this study aims to analyse the effectiveness of project-based learning in improving students' creativity. This research uses the Classroom Action Research (PTK) method which consists of the stages of planning, implementation, observation, and reflection. Data were collected through observation, interviews with teachers and students, and analysis of students' project results. The results showed that the implementation of project-based learning significantly improved students' engagement and creativity. Students became more active in the exploration of ideas, showed improvement in problem-solving skills, and were more confident in expressing their ideas. However, challenges in implementing this method include teacher readiness, sufficient time allocation, and availability of adequate resources. Therefore, support from schools and the development of a more systematic learning strategy are needed for this method to be optimally implemented